SW1353 연골세포에서 기능 성분이 증대된 보스웰리아 검레진 추출물의 항골관절염 효과 연구 - 정재인(Jae In Jung); 이현숙(Hyun Sook Lee); 김룡(Ryong Kim); 김은지(Eun Ji Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구는 인체유래 연골세포인 SW1353 세포에 IL-1β를 처리하여 유도한 골관절염 세포 모델에서 인도산 보스웰리아 검레진을 주정으로 추출 후 지방 제거 공정을 추가하여 제조한 보스웰리아 검레진 추출물인 FJH-UBS의 항골관절염 효능을 평가하기 위해 실시하였다. SW1353 세포에 IL- 1β 처리 시 염증매개물질인 NO/iNOS, PGE2/COX-2, IL- 6 및 TNF-α 발현과 연골 기질 분해에 기여하는 MMPs (MMP-1, MMP-3, MMP-13) 발현이 증가하였다. 또한 IL-1β 처리에 의해 연골의 구성성분인 aggrecan과 type Ⅱ collagen 발현이 감소하였다. FJH-UBS는 IL-1β에 의해 증가한 NO/iNOS, PGE2/COX-2, IL-6, TNF-α, MMP- 1, MMP-3 및 MMP-13 발현을 감소시켰고, IL-1β에 의해 감소한 aggrecan과 type Ⅱ collagen 발현을 증가시켰다. 골관절염의 염증반응과 연골 퇴화를 조절하는 주요한 신호전달체계인 MAPK(ERK, p38, JNK)와 NF-κB(p65, Iκ-Bα)의 인산화는 IL-1β에 의해 증가하였고, 이는 FJH-UBS에 의해 감소하였다. 이 결과는 FJH-UBS가 활성화된 MAPK와 NF-κB 신호전달체계를 억제하여 염증매개물질(NO, PGE2, IL-6, TNF-α) 및 MMPs(MMP-1, 3, 13)를 억제하고 연골 기질(aggrecan, collagen) 분해를 억제하여 항골관절염 효능을 발휘함을 나타내며, 이는 FJH-UBS를 관절 및 연골 건강 개선제로의 활용 가능성을 제시한다. Boswellia serrata (BS) is widely employed for the treatment of several diseases such as arthritis, rhinitis, asthma, and several cancers. The present study investigates the anti-osteoarthritis activity and the underlying mechanism of the ethanol extract of BS gum resin (FJH-UBS) enriched with keto-β-boswellic acid and 3-O-acetyl-11-keto-β-boswellic acid compared to the conventional BS extract by the additional process of oil removal with hexane. An in vitro osteoarthritis-like model was established using interleukin (IL)-1β-stimulated human SW1353 chondrocytes. The SW1353 cells were stimulated with IL-1β (10 ng/mL) and treated with FJH-UBS (0∼20 μg/mL) for 24 h. FJH-UBS reversed the IL-1β-induced increase in the protein and mRNA expressions of nitric oxide/inducible nitric oxide synthase, prostaglandin E2/cyclooxygenase, IL-6, tumor necrosis factor-α, matrix metalloproteinase (MMP)-1, MMP-3, and MMP-13, and reversed the IL-1β-induced downregulation of aggrecan and type II collagen. In addition, FJH-UBS reversed the IL-1β-induced increases in p65 nuclear factor-κB (NF-κB), inhibitor-κ-Bα, and the mitogen-activated protein kinase (MAPK) family (extracellular signaling-regulated kinase, p38, c-jun-N-terminal-kinase) phosphorylation, suggesting an anti-inflammatory activity mediated by blocking these key signaling transduction pathways. These results indicate that FJH-UBS is a potential therapeutic agent for osteoarthritis, exerting its effect via inhibition of the IL-1β-induced inflammation and inhibiting extracellular matrix degradation by suppressing the NF-κB and MAPK pathways. KCI Citation Count: 2